A multi-tag anti-collision protocol based on 8-ary adaptive pruning query tree. (November 2018) - Chu, Ming; Qian, Zhihong; Wang, Xue
In order to solve the problem of multi-tag anti-collision in radio frequency identification systems, a multi-tag anti-collision protocol based on 8-ary adaptive pruning query tree is proposed in this article. According to Manchester code, the highest collision bit can be detected. In the process of tag identification, the protocol only locks the target on the three consecutive bits which start from the highest collision bit. The protocol has two tag identification mechanisms, and which one is chosen is determined by the value of collision coefficient. Using the collision information characteristics of the three bits, idle timeslots are evitable, and some collision timeslots are eliminated at the same time. The 8-ary adaptive pruning query tree protocol fully takes into account several important performance indicators such as the number of query timeslots, communication complexity, transmission delay, and throughput. Both theoretical analysis and simulation results show that this protocol performs better than other tree-based anti-collision protocols. The throughput of 8-ary adaptive pruning query tree protocol remains approximately 0.625.